133 A follow up of lipid profile assessment in patients with ST elevation myocardial infarction treated with percutaneous coronary intervention (PCI) - Are we missing patients with familial hypercholesterolaemia?. (17th July 2020) - Elgerray, Samir; Harper, Nicole; Jesudason, Daniel; Al-Ubaidi, Firial; Prinsloo, Peter; Divyateja, Hrushikesh; Uddin, Akhlaque
Abstract : Background: Familial hypercholesterolaemia (FH) is an important and under-diagnosed cause of premature cardiovascular disease. It is recommended that all patients with suspected myocardial infarction should have their lipid profile measured on admission. The advantages of statins have been indisputably demonstrated in secondary prevention and the greatest benefit has been established with early intensive therapy following acute coronary syndrome. Aims and Methods: The main objective was to improve assessment of lipid profile in the acute setting in all patients admitted with ST-elevation myocardial infarction (STEMI). Through this, there was capacity to aid in recognition and diagnosis of familial hypercholesterolaemia (FH). A retrospective assessment of all patients referred via the primary percutaneous intervention (PCI) pathway to the Trent Cardiac Centre between April 2016 and April 2017. We evaluated whether a random in-patient lipid profile was obtained, if patients met biochemical Simon Broome criteria for FH (total cholesterol >7.5 mmol/L +/- low-density lipoprotein cholesterol >4.9 mmol/L); were they were referred to a Lipid Clinic; was a statin prescribed and followed up was also investigated. We then implemented several changes throughout the cardiology department. These included the development of an electronic blood request order set including lipid profile for primary PCI patients. We also designed a new clerking proforma reminding clinicians to check the lipid profile. Information posters were distributed throughout the department and educational departmental sessions were held. A re-assessment was then performed of all patients between April 2018 and April 2019. Results: The original data showed that from the 383 patients referred, 52 did not meet inclusion criteria. Of the remaining 331 patients, 67 (20%) patients did not have lipid profile checked as an in-patient. Of the 264 patients who had a lipid profile checked, 8 (3%) met biochemical Simon Broome criteria and 0 were referred to lipid clinic. Following the intervention, the re-audit showed that from the included 284 patients, 20 (7%) patients did not have a lipid profile checked as an in-patient. Seven (3%) of the 264 patients who had an in-patient lipid profile met biochemical Simon Broome criteria; 1 (14%) was referred to lipid clinic. Conclusion and Interpretation: These results demonstrate an improvement in assessment of lipid profile in patients admitted with STEMI from 80% to 93%. There was also advancement in referral of patients to specialist lipid clinic from 0% to 14%. It is estimated that less than 10% of the FH population in the UK have been diagnosed. Greater efforts must be made to not only perform lipid profiles in patients admitted with STEMI, but also to ensure that these results are checked and appropriate clinical decisions are made. These simple changes could potentially have hugely beneficial clinical and financial implications. Conflict of Interest: None